All aboard: a train tastic tale of railway adventure - Brown, Scott (igloo UK, 2017)
"All Aboard" is a lively children's book that invites young readers to join an exciting journey on a train. The story typically features a colorful cast of characters as they board the train, exploring various landscapes and engaging in fun activities along the way. With catchy rhymes and vibrant illustrations, the book captures the thrill of adventure and the joy of travel. It encourages imagination and curiosity, making it an engaging read for children who love trains and exploration.